Barriers in Implementing TQM in Secondary Schools: A comparison between privately-owned and government-owned schools of Pakistan - Aziz, Abdullah; Hussain, M. Jafar; Ahmad, Sayed Fayaz; Nadeem, AbidHussain; Ibrahim, Muhammad; Qayyum, Abdul; Amjad, Sana (The journal of contemporary issues in business and government, 2021)
Quality in education is essential in the overall development of a nation. In an underdeveloped nation, such as Pakistan, the focus of quality is usually on primary or tertiary education which overlookssecondary schooling. In this regard, theperceived causes of poor implementation of total quality management in secondary schooling were studied. Faculties of both public and private schools were surveyed with respect to six different barriers that are responsible for lack of quality in the education sector. Each analyzed barrier pointed out the extent of the educational quality. It also highlights the similarity in educational qualitydoes not depend upon the ownership of the school. Reasons for poor perception of quality management systems in the education sector are also discussed along with recommendations against each barrier.